Snakes and Ladders Game Innovation on Increasing Knowledge and Behavior Changes About Oral Dental Health in Children at Al Barokah Orphanage - Sukini, Sukini; Ratuela, Jeineke E; Faturrohman, Fuad; Suyatmi, Dwi (Poltekkes Kemenkes Yogyakarta, 2022)
The traditional game of snakes and ladders is a local wisdom, educative for children to play while learning so that it can be used to increase knowledge and skills of dental health. The purpose of this study was to design an innovative snake and ladder game that serves to increase knowledge about dental and oral health.This research is the development of existing research. In this study, an innovation of the snake and ladder game was developed for dental and oral health. Research designquasi experiment by design Pretest-Posttest control group design.The sample is elementary school age children at the Al Barokah Orphanage. 17 children became the control group and 17 as the neutral group. The independent variable is Snake Ladder Game Innovation, the dependent variable is knowledge and changes in dental health behavior, with instruments in the form of a questionnaire and a check list of 25 questions on an ordinal scale of pre-test and post-test instruments..The most pre-test results with sufficient knowledge category are 22 respondents (64.7 %), the most final knowledge score (Posttest) with good knowledge category is 26 respondents (76.4%). The results of the Mann Whitney statistical test showed that there was a difference between the experimental group and the control group on dental and oral health knowledge with a value of 0.02 < 0.05.The results of the Wilcoxon Test statistical test showed that there was